Case Report: Chondrosarcoma Located in the Thoracic Vertebra - Akpolat, Nusret; Ucer, Ozlem; Kaplan, Metin (Journal Neurological Sciences, 2011)
Chondrosarcomas are the primary malignant tumor of the bone; they are characterized by neoplastic cartilage production and are the third most common type of bone tumors. They are seen in males over 40 years. Chondrosarcomas, which primarily involve the pelvis, proximal femur, proximal humerus, shoulder belt and costae, are rarely located in the vertebrae. Our case, a 53-year-old female patient presented in the clinic complaining from increasingly intense lumbar pain, as well as pain and numbness in both legs for 2 months. Her examinations revealed a mass of 65x58 mm on the T1 vertebra corpus, pressing upon the cord, extending towards the mediastinum and causing spinal stenosis. The biopsy taken from the mass was diagnosed as chondrosarcoma by histopathology, and corpectomy was performed. As chondrosarcoma is rarely located on the vertebrae, we aimed to discuss the clinical, radiological and histopathologic results of our case in the light of literature data.
Torakal vertebra yerleşimli kondrosarkom olgu sunumu
Keywords: Thoracic vertebra; chondrosarcoma